2022
DOI: 10.3389/fvets.2022.889117
|View full text |Cite
|
Sign up to set email alerts
|

From Soundwave to Soundscape: A Guide to Acoustic Research in Captive Animal Environments

Abstract: Sound is a complex feature of all environments, but captive animals' soundscapes (acoustic scenes) have been studied far less than those of wild animals. Furthermore, research across farms, laboratories, pet shelters, and zoos tends to focus on just one aspect of environmental sound measurement: its pressure level or intensity (in decibels). We review the state of the art of captive animal acoustic research and contrast this to the wild, highlighting new opportunities for the former to learn from the latter. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 163 publications
0
13
0
Order By: Relevance
“…Unfortunately, we do not have estimates of parameters such as "annoyance" for nonhuman primates. What is considered "noise" may also depend on a species' hearing capacities (Clark & Dunn, 2022) and pied tamarin audiograms are currently unavailable. Even though we lack such clearcut values to establish what constitutes noise for pied tamarins, we found that when sound levels were relatively higher, the probability of pied tamarins emitting a long call increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, we do not have estimates of parameters such as "annoyance" for nonhuman primates. What is considered "noise" may also depend on a species' hearing capacities (Clark & Dunn, 2022) and pied tamarin audiograms are currently unavailable. Even though we lack such clearcut values to establish what constitutes noise for pied tamarins, we found that when sound levels were relatively higher, the probability of pied tamarins emitting a long call increased.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that in our study, we characterized noise in terms of amplitude. However, noise is complex and variable in terms of spectral and temporal signatures (Clark & Dunn, 2022; Gill et al, 2015; Neo et al, 2014). Howler monkeys, for instance, respond more to aerial traffic than other human‐produced noises (Gómez‐Espinosa et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Human presence can influence the soundscape experienced by animals in zoos. In general, sound sources in zoos can be separated into four broad categories: 1) permanent sources of anthropogenic sound, such as heating, ventilation, and air conditioning (HVAC) systems; 2) temporary anthropogenic sound from maintenance, construction, and other events; 3) human speech and footfall; and 4) sounds produced by other animals (Clark & Dunn 2022). Three of these four categories are related to human presence and anthropogenic sound sources, suggesting that the constant presence of humans is likely to have a significant impact on the soundscape.…”
Section: Introductionmentioning
confidence: 99%
“…As such, animals in captivity may experience soundscapes that differ from those in the wild (Lara & Vasconcelos 2019). In addition, the contributions of different sound sources are likely to differ among zoos and enclosures, and, therefore, soundscapes are also likely to vary among captive environments (Clark & Dunn 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation